Importance of ethical training of medical students - Izaguirre, Manuel (2019)
Understanding the importance of the ethical training of medical students, requires analyzing the current reality of medical education to determine what ethical and moral criteria medical students should be instilled during their training so that they are excellent professionals with ethical responsibility and legal by focusing teaching on the student as a person, on technical excellence to be a good doctor, and on moral excellence, to be a good doctor. Therefore, you must understand that the patient as a person and their context should be the axis of medical care by complementing bi-directionally with science and humanism, making the patient the supreme end of medicine and not as a simple carrier of diseases, seeking their well-being, not causing harm, respecting their autonomy and justice in decisions that must be prudent, responsible and moral.